Achatina (Lissachatina) fulica Bowdich: its molecular phylogeny, genetic variation in global populations, and its possible role in the spread of the rat lungworm Angiostrongylus cantonensis (CHEN) - Fontanilla, Ian Kendrich C. (2010)
The Giant African Snail, Achatina (Lissachatina) fulica Bowdich, is a tropical crop pest species with a widespread distribution across East Africa, the Indian subcontinent, Southeast Asia, the Pacific and the Caribbean. It is also a known intermediate host of the rat lungworm, Angiostrongylus cantonensis, which can infect humans and cause eosinophilic meningitis. The phylogenetic position of A. fulica within the Achatinoidea and the Achatinidae was investigated using segments of the nuclear ribosomal (r) RNA cluster, actin and histone 3 genes and the mitochondrial CO1 and 16S rRNA genes. Results from molecular data support the monophyly of the Achatinidae based on the taxa surveyed as well as the morphological distinction of the Eastern Achatina (Lissachatina) from the Western and Central Achatina (Achatina); Lissachatina should therefore be elevated to genus status. The results also show non-monophyly of the Coeliaxidae, Ferussaciidae and Subulinidae; the taxonomy of these families must therefore be reassessed. The extent of genetic diversity in global A. fulica populations was also determined using an SSCP molecular marker developed from the 16S rRNA gene. Results reveal only one haplotype (C) emerged from East Africa and spread globally. The rat lungworm (Angiostrongylus cantonensis) has a parallel distribution with A. fulica, and the possible role of the snail in the spread of the parasite is investigated using a molecular marker derived from the small subunit (SSU) rRNA gene. A survey of the parasite within the route of dispersal of A. fulica detected A. cantonensis only in the Philippines and the French Polynesian territory of Tahiti, the latter of which being the first reported case of A. cantonensis infection for Achatina fulica in that territory. Due to the limited sampling of the snail and the patchy distribution of the parasite, there are insufficient data at this time to assess the role of Achatina fulica in the spread of Angiostrongylus cantonensis.